Effects of Carbon Tax on Urban Carbon Emission Reduction: Evidence in China Environmental Governance - Zhao, Aiwen; Song, Xiaoqian; Jiajie, Li; Yuan, Qingchun; Pei, Yingshun; Li, Ruilin; Hitch, Michael (MDPI AG, 2023)
Carbon tax is an important economic instrument in achieving the goal of carbon emission reduction and sustainable development. This paper investigates the effects of carbon tax on carbon emission reduction in China. First, a non-competitive input–output table for Carbon Emissions of 28 sectors in China after Carbon Tax was established, based on the “2018 China Non-competitive Input–Output Table (42 Sectors)” and the carbon emission data of sectors provided by China Carbon Emission Accounts and Datasets (CEADs). Then, an input–output price model was established to study the changes on product price, GDP, employment, and carbon dioxide emissions of 28 sectors after carbon taxing ranged from 10 to 200. When the carbon tax rate reaches 200 yuan/ton, the inflation rate will be 5.907%, the total GDP will be decreased to 1.910%, the total labor force will be decreased to 1.744%, and the total carbon emission reduction rate will be increased to 8.171%. Results showed that with the increases in carbon tax, the inflation rate was increased, the rate of carbon emission reduction was increased, and the negative effects on GDP and employment were also increased. Suggestions on policy making, such as combination of carbon taxing and carbon trading, dynamic adjustment mechanism, tax neutrality, and forcing active carbon reduction, were proposed to minimize the adverse effect of levying carbon tax. The results from this paper would provide a reference for the policy making on carbon management.